Fistula First – Are We There Yet? A Multicenter study. - Omer Sabir; Muhammad Mohsin Riaz; Kashif Rafique; Noman Anjum; et al. (Pakistan Journal of Kidney Diseases, 2021)
“Fistula First” for initiation of hemodialysis (HD) has been touted vigorously over the last few years. Vascular Access (VA) – Arteriovenous Fistula (AVF) and Arteriovenous Graft (AVG) are considered to be the life line of patients on maintenance hemodialysis. In our resource constrained setups, patient refusal and delay in formation of the VA as well as its failure is rather common. Objective: The objectives of our study were to document the frequency of use of temporary vascular access at the initiation of dialysis, prevalent VA. Methods: Total of 394 patients undergoing hemodialysis in six hemodialysis units in Lahore, Pakistan were included in the study. Patients were interviewed and records checked for the vascular access used to initiate hemodialysis and types and number of vascular access made. Results: Majority (n=350, 88.8%%) of the patients started their dialysis with temporary catheters. At the time of collection of data most of the patients had AVF (n=335, 85%) followed by permanent catheter (n = 28, 7.1%), AVG (n=14, 3.5%) and temporary vascular access (n=17, 4.3%). More than half (59.6%, n=208) of the patients with Permanent VA (i.e. AVF and AVG) had at least one access failure and 22.9% (n=80) patients had more than one failure. Delay in access formation correlated significantly although weakly with VA failure rate. Conclusions: Our patterns of vascular access indicate delay in formation of VA resulting in a high use of temporary catheter for initiation of maintenance hemodialysis and a high rate of failure of VA.